Proceedings of the Twenty-Fifth Hawaii International Conference on System Sciences 1992
DOI: 10.1109/hicss.1992.183351
|View full text |Cite
|
Sign up to set email alerts
|

Development of measures for studying emerging technologies

Abstract: The objective of this paper is to describe the process of construct validation and instrument development, and to discuss recent efforts within the Management Information Systems Literature in this area. It first reviews the issues of construct validity, describing the criteria by which the process and output of validation g i r t s can be assessed. It then comiders three studies which concentrated on developing instruments to measure the factors which aflect the adoption of new information technologies. mese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…However, the complex nature of these problems are becoming even more and more challenging for SMEs and this study especially if the framework is vital for practitioners that are involved in decision-making and seek to develop models for IT application (Derick and West, 2003). Therefore, the framework could be useful to micro-businesses in having a more indepth insight on the factors shaping DMD as well as a strong justification for the courses of action (Benbasat and Moore, 1992) in DMD adoption process. The practical insight can be utilised by SMEs to create awareness on the use of DMD and how to successfully adopt the new devices and avert some of the challenges they may be encountering in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complex nature of these problems are becoming even more and more challenging for SMEs and this study especially if the framework is vital for practitioners that are involved in decision-making and seek to develop models for IT application (Derick and West, 2003). Therefore, the framework could be useful to micro-businesses in having a more indepth insight on the factors shaping DMD as well as a strong justification for the courses of action (Benbasat and Moore, 1992) in DMD adoption process. The practical insight can be utilised by SMEs to create awareness on the use of DMD and how to successfully adopt the new devices and avert some of the challenges they may be encountering in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the framework could also serve as a frame of reference to SMEs seeking to have a deep insight and a common understanding of the factors influencing the adoption of mobile marketing devices. Also, the framework could be used by managers for a strong justification for the courses of action (Banbaset and Moore, 1992; Macredie and Mijinyawa, 2011) in the adoption of mobile marketing technology. SME managers and other decision-makers could use the argument in the study and the practical insight in this study to create awareness among staff on the benefits and challenges associated with the use of mobile marketing technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The third construct is compatibility, which identifies and explains the extent to which an OSS is perceived to fit with the adopter's existing values and software policies, previous experiences and relevant skills, or current IT needs (Benbasat and Moore 1992;Rogers 1995;Taylor and Todd 1995a,b)). An example is of perceptions related to functionality (Fitzgerald and Kenny 2003;Forrester Consulting 2007;Overby et al 2006), which was identified to fit with the feature of 'current IT needs' and can be argued to fit with 'existing values'.…”
Section: Attitudinal Belief Structuresmentioning
confidence: 99%